Disentangling the Archaeology of textile production in Viking Age Iceland - Viðarsdóttir,Ásta Rakel (2025)
This thesis investigates textile production in Viking Age Iceland. While in the past two decades a significant amount of research has been done on the textiles that have been recovered during archaeological excavations, research on the textile production itself remains underexplored. Current thinking assumes that production followed a standard household-based model across Iceland, but this interpretation has never been thoroughly evaluated. In recent years, new excavations are starting to suggest possible regional-scale variation in the organization of textile production, raising important new research questions that await further investigation. To close this gap in knowledge, this thesis employs an explicit model-based and multiscalar approach to clarify how textile production was organized in Viking Age Iceland. The overarching goal is to assess whether farms in different parts of Iceland followed one common strategy of textile production. The model is applied at three analytical scales to evaluate regional variation in textile production based on the distribution and quantity of textile related tools uncovered through archaeological excavations: • Household scale Site based analysis focused on the recently excavated site of Fjörður in the east of Iceland, which has yielded the largest known assemblage of textile production artifacts in Iceland. This scale allows for detailed insight into household-level textile practices. • Inter-regional scale Examines five archaeological sites from different areas of Iceland to identify regional differences in textile production during the Viking Age. • North Atlantic core-periphery scale Places Icelandic textile production in a broader North Atlantic context, comparing it with evidence from other regions within the Viking World. Iceland is considered remote but not the remotest part of this network, offering a valuable perspective on how peripheral locations contributed to and diverged from broader textile production trends. The results from this thesis are that while all textile production in Iceland was household based, it was not all produced in the same intensity. Some farms showed hardly any signs of textile production while the site of Fjörður showed signs of intense textile production consistent with household industry. Additionally, this analysis has shown that there was, according to the archaeological evidence available today, a regional difference in textile production in Iceland where production in the East surpassed the other regions of the island.